Validation of ash/dust detections from SEVIRI data using ACTRIS/EARLINET ground-based LIDAR measurements - Falconieri A.; Papagiannopoulos N.; Marchese F.; Filizzola C.; Trippetta S.; Pergola N.; Pappalardo G.; Tramutoli V.; Mona L. (Remote Sensing, 2020)
Twotailored configurations of the Robust Satellite Technique (RST) multi-temporal approach, for airborne volcanic ash and desert dust detection, have been tested in the framework of the European Natural Airborne Disaster Information and Coordination System for Aviation (EUNADICS-AV) project. The two algorithms, running on Spinning Enhanced Visible Infra-Red Imager (SEVIRI) data, were previously assessed over wide areas by comparison with independent satellite-based aerosol products. In this study, we present results of a first validation analysis of the above mentioned satellite-based ash/dust products using independent, ground-based observations coming from the European Aerosol Research Lidar Network (EARLINET). The aim is to assess the capabilities of RST-based ash/dust products in providing useful information even at local scale and to verify their applicability as a "trigger" to timely activate EARLINET measurements during airborne hazards. The intense Saharan dust event of May 18-23 2008-which affected both the Mediterranean Basin and Continental Europe-and the strong explosive eruptions of Eyjafjallajökull (Iceland) volcano of April-May 2010, were analyzed as test cases. Our results show that both RST-based algorithms were capable of providing reliable information about the investigated phenomena at specific sites of interest, successfully detecting airborne ash/dust in different geographic regions using both nighttime and daytime SEVIRI data. However, the validation analysis also demonstrates that ash/dust layers remain undetected by satellite in the presence of overlying meteorological clouds and when they are tenuous (i.e., with an integrated backscatter coefficient less than ~0.001 sr-1 and with aerosol backscatter coefficient less than ~1 × 10-6 m-1sr-1). This preliminary analysis confirms that the continuity of satellite-based observations can be used to timely "trigger" ground-based LIDAR measurements in case of airborne hazard events. Finally, this work confirms that advanced satellite-based ...